Seminar Konsultasi Jurusan di SMA Nurul Iman Limau Manis Kecamatan Tanjung Morawa Kabupaten Deli Serdang Bersama - Rahmadani Rahmadani; Novi Handayani Simbolon; Nurhaflah Soraya; Sondang Beatrix Siahaan; Khanti Listya (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2023)
One effort to realize the quality of human resources is through education. In college, students are focused on one area that they are interested in and will later apply in the world of work. High school students who are about to graduate definitely want a good career for their future, giving rise to intense competition among students throughout Indonesia to be able to enter their favorite university and the major they dream of. Problems related to students' lack of knowledge about various departments in higher education are resolved through counseling or socialization methods using material presentation techniques and followed by discussion sessions. This activity was carried out in order to provide information to all Nurul Iman Limau Manis High School students who will continue their education to college. With this, they can find out the various specifications of majors which are the place where the student learning process takes place as well as the place where the mission and function of higher education are realized and can measure the abilities they have which can then be adjusted to the majors and universities of their interest.